The dialectic of globalization and social transformation of Silariang in Makassar, Indonesia - NONCI, NURMI; HARIFUDDIN, HARIFUDDIN; AZUZ, FAIDAH; ISKANDAR, Iskandar; Arifin, Ansar (ETNOSIA : Jurnal Etnografi Indonesia, 2023)
Globalization contribute to the socio-cultural construction and transformation of society. This study aims to analyze the construction and social transformation of silariang among Makassar people in South Sulawesi Province, Indonesia. The research uses a case study approach. Data were obtained through in-depth interviews, participant observation, and documentation studies. The results of the study show that siri’ (means dignity or shame or both at the same time) as the core value of Makassar people has a prominent relationship with silariang cases. Further, the globalization has changed the the world of view of the local community, particularly the younger generations, making them started to open minded. This change has lead them into a socio-cultural transformation. If in the past Makassar people extremely uphold the siri’ value exemplified by silariang, nowadays, people are more open to the alternative option called nikah siri or unregistered marriage. It also shows that the siri’ concept is fluid.